Central corneal thickness in eyes with pseudoexfoliation syndrome in Kashmir Valley - a hospital based study - Ahmad Sofi, Ishfaq; Nawaz, Shah; S. Wani, Junaid (International Journal of Medical Research and Review, 2015)
Introduction: Pseudoexfoliation syndrome (PEX) is characterized by the production and accumulation of extracellular granular fibrillar material in many ocular tissues. Pseudoexfoliation has been closely associated with glaucoma and raised intraocular pressure (IOP) is the most important known risk factor for glaucoma. Central corneal thickness (CCT) may affect the accuracy of IOP measurements. Thus, it is possible to underestimate/overestimate the IOP reading in the PEX syndrome and overlook an early glaucomatous damage. The aim of our study was to determine the central corneal thickness (CCT) in eyes with pseudoexfoliation (PEX). Methods: Total 2076 eyes (of 1224 patients) with pseudoexfoliation on clinical examination were enrolled in this prospective clinical study and CCT was measured in each eye using specular microscopy. Results: Mean CCT (????m) in eyes with Pseudoexfoliation was 525.43 ± 34.27. CCT in eyes with Hypertensive PEX (513.2 ± 27.8) and PEX Glaucoma (509.22 ± 29.76) was significantly thinner than in eyes with Normotensive PEX (528.17± 30.33) (P = 0.001, P = 0.0001, respectively). There was no significant difference in CCT between the fellow eyes in cases of unilateral pseudoexfoliation (P = 0.54). Conclusion: Mean central corneal thickness (CCT) in eyes with pseudoexfoliation is 525.4 µm and CCT is significantly thinner in Hypertensive PEX as well as Glaucomatous PEX eyes than Normotensive PEX eyes.